Tibial Plateau Leveling Osteotomy in Dogs: an Ex Vivo Comparative Study of Knee's Surrounding Structures Protection Methods - Costa, Rodrigo Casarin [UNESP] (2022)
Background: Cranial cruciate ligament failure is one of the leading causes of pelvic limb lameness in dogs and one of the most recommended treatments is tibial plateau leveling osteotomy (TPLO) surgery. However, this procedure may lead to some complications as fractures of the fibula, laceration in varying degrees of the popliteal vasculature and its branches, neuropraxia, neurotmeses, among others. The goals of this study were to compare the effectiveness of 8 methods used during TPLO, to prevent damage to the cranial tibial artery, fibula, tibial and fibular nerve (surgical compresses, specific surgical retractors I and II and an osteotomy technique variation). Materials, Methods & Results: A total of 40 canine cadavers weighing 25.9 +/- 3.7 kg were submitted to TPLO. Animals were previously prepared with 1: 4 barium red latex solution, to provide radiopacity of arteries surrounding the knee (n = 80). TPLO was performed using 8 methods to protect the cranial tibial artery, fibula, and tibial and fibular nerves. Each method was used in one of the knees of 5 animals. The contralateral knee was maintained as a control (without protection). The knees were radiographed in orthogonal projections before and after the osteotomies and then anatomically dissected. The evaluated structures were photographed, and the images sent to four blind evaluators (visual macroscopy) to classify the possible injuries. The highest incidence of injuries was identified when protection methods were used. However, this difference was not significant (P > 0.05). No significant differences regarding efficacy were found between all 8 protection methods. Discussion: In this study, the total incidence of injuries following TPLO was 20% was much higher than that presented in the literature which indicates when considering only intraoperative injuries. The dogs cadavers tissue resistance and stiffened latex may have predisposed the osteotomy injury, as soft tissues with greater flexibility are less susceptible to trauma caused by the oscillatory saw. When compared to others cadaveric studies that also evaluated the efficacy of surgical dressings to protect the cranial tibial artery, during TPLO, we also find a higher incidence of damage. Maybe the limb's position was responsible for this difference, once in the after mentioned researches the limb was positioned suspended to simulate a dorsal decubitus position and we choose the limb position with the lateral face resting on the surface of the operating table, and this may have provided extra pressure from the structures towards the osteotomy saw, increasing the occurrence of those damages. Although the present study did not reveal a significant difference for the use of protection methods, we believe that the dimensions of the compresses used herein may have contributed to a higher incidence of injuries. They probably increased the tissue trauma needed for their allocation and led to a lower positioning accuracy for the isolation of these structures. Maybe for the same reason, the specific type II surgical retractor was the only shield that, observationally, did not increase the occurrence of injuries, once less dissection was required to allocate it. The difference in geometric dimensions between the retractors may justify the superiority of the retractor II, since it allows a more careful and apparently less traumatic allocation. Performing TPLO without adopting these protection methods did not lead to a higher risk of injury to the cranial tibial artery, fibula, and tibial and fibular nerves.